Domain Name Disputes and Their Resolution under UDRP Route: A Review - Singh, Harman Preet (Archives of Business Research, 2018)
Domain names have a dual role in today’s internet driven market place – to map IP addresses and to act as identifier of trademark of a company. Unlike trademarks, domain names are not sufficiently protected by the laws of a country. There is no uniformity to protect domain names among the laws of various countries. In order to protect the domain names and bring uniformity, ICANN developed the Uniform Domain Name Resolution Policy (UDRP). In this research, the various kinds of domain name abuses are identified. The application of UDRP, domain name registration process and dispute resolution service process are examined. The major domain name dispute cases resolved under UPRP by WIPO are studied. It has been found that UDRP is applicable to generic top level domains (gTLDs) and new gTLDs. It is much less relevant for country code top level domains (ccTLDs). The losing party still has the option of appealing to a court of competent jurisdiction in case of gTLDs and new gTLDs. However, this option is seldom exercised. In order to protect the domain names in a better way, there is a need to bring uniformity to domain name laws of various countries. ICANN should formulate a model domain names dispute resolution law for adoption by various countries. Also, there is a need to strengthen the UDRP.